Quality of life among diabetics: A cross-sectional study in a tertiary care center of Rohtak, Haryana - Meena Rajput; Yashodha Arivarasan; Aereosonova Khongsit; Rajesh Rajput (Wolters Kluwer Medknow Publications, 2020)
Introduction: The most severe health threats dominating the low- and middle-income countries are no longer the dreaded communicable diseases; but, they are everyday diseases due to changes in lifestyle, which are the noncommunicable diseases. Quality of life (QOL) is defined by the World Health Organization as an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards, and concerns. QOL assessment in health system is a multidimensional construct that can be measured by evaluating objective levels of health status filtered by the subjective perceptions and expectations of the individual. Aim and Objective: To assess the QOL among diabetics attending the endocrine outpatient department (OPD) in a tertiary care hospital of Haryana. Materials and Methods: A hospital-based cross-sectional study was conducted at endocrinology OPD of Pt. B. D. Sharma PGIMS Rohtak, Haryana from May 2014 to April 2015. Five hundred diabetics (Type 1 and 2) were recruited for the study. Patients registered on the day of interview were selected using systematic random sampling. A predesigned, pretested, semi-structured schedule which included sociodemographic variables of the study participants along with information about family history of diabetes was filled by interviewing the study subjects in their vernacular language individually. Generic instrument, SF-36 v2 was used to assess the QOL. Results: The mean age of the study participants was 50.41 ± 9.1 years. The mean disease duration was 6.12 ± 5.55 years. Majority of our respondents belonged to Hindu religion (97.4%). The mean scores for the bodily pain domain (79.52 ± 28.15) and social functioning domain (76.47 ± 26.10) of QOL were the highest. Conclusion: The mean scores for the bodily pain domain and social functioning domain of QOL were the highest. Assess the QOL in patients with diabetes by measuring the multiple domains involving physical, psychological and social aspects.